Technology For the Development of Writing Skills in Foreign Language - Yusupova Nafisa Karimullayevna (Genius Journals, 2021)
The article considers writing as an independent type of speech activity. The control of the formation of writing skills, the technology of formation of foreign language writing skills of language students is analyzed. It also analyzes the types of exercises as reproductive, reproductive-productive and productive, focused on the ability to express their thoughts in writing.
Keywords: Writing; Types of Exercises; Expression of Thought; Teaching Graphics